Ludwig´s Angina in the diabetic patient: evidence in literature (Research, Society and Development, 2020)
Introduction: Ludwig’s Angina (LA) is a head and neck infection potentially fatal, which affects simultaneously submandibular, sublingual, and submental spaces. Diabetes mellitus (DM), due to its immunological and microvascular repercussions, can predispose to LA or modify the patient's response to this infection. Objective: to evaluate the impact of diabetes mellitus on patients with LA. Methods: This study is a literature review in which a search strategy was proposed that used MEDLINE as a database, accessed via PUBMED, limited to the English language and publications between 1954 to 2020. In the research, the following descriptors: “Ludwig's angina” and “diabetes”. Case reports and observational studies approach about Ludwig's angina in diabetic patients were included. Results: 26 articles were found and, after read the abstract, 12 articles were excluded, because there was no relation between LA and DM. Concerning to time of hospital stays, the patients diagnosed with hyperglycemia have a higher hospital stay, due to complications and clinical follow-up. The most common group of microorganisms isolated in diabetic patients was Klebsiella pneumoniae. The antibiotic therapy most commonly used empirically was an association with amoxicillin, clavulanate potassium and metronidazole. Conclusion: It’s possible to observe that Ludwig’s Angina had your clinical evolution modified for diabetes mellitus. The complications involving the association between DM and LA occurs as many diabetic patients without glycemic control, as diabetic patients controlled, to a lesser extent.